The Influence of Communication and Work Motivation on the Performance of Cementing Department Employees at PT Adis Dimension Footwear at Tangerang Regency - Fitriani, Annisa; Soebadio, Bizzma Buana Amriki; Setiawan, Temmy (IJOSPOL - International Journal of Social, Policy and Law, 2026)
This study aims to examine the effect of communication and work motivation, both partially and simultaneously, on employee performance in the Cementing Department at PT Adis Dimension Footwear, Tangerang Regency.This research employed a quantitative descriptive method with a survey approach.The population consisted of all employees in the Cementing Department at PT Adis Dimension Footwear, Tangerang Regency. The sample size was 61 respondents, determined using a simple random sampling technique, while the Slovin formula was applied to calculate the sample size. Data were collected through questionnaires and analyzed using multiple linear regression analysis with the assistance of SPSS version 26.The results indicate that: (1) partially, communication has a significant effect on employee performance in the Cementing Department at PT Adis Dimension Footwear, Tangerang Regency, as shown by a t-value of 2.474, which is greater than the t-table value of 2.002, with a significance value of 0.000 < 0.05; (2) partially, work motivation has a significant effect on employee performance, indicated by a t-value of 4.781, which is greater than the t-table value of 2.002, with a significance value of 0.000 < 0.05; and (3) simultaneously, communication and work motivation have a significant effect on employee performance, as evidenced by an F-value of 15.368, which is greater than the F-table value of 3.16, with a significance value of 0.000 < 0.05.Based on these findings, it can be concluded that communication and work motivation, both partially and simultaneously, have a significant influence on employee performance in the Cementing Department at PT Adis Dimension Footwear, Tangerang Regency.